2010
DOI: 10.1111/j.1365-2958.2010.07085.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the gate regions in the primary structure of the secretin pIV

Abstract: SummarySecretins are a family of large bacterial outer membrane channels that serve as exit ports for folded proteins, filamentous phage and surface structures. Despite the large size of their substrates, secretins do not compromise the barrier function of the outer membrane, implying a gating mechanism. The region in the primary structure that forms the putative gate has not previously been determined for any secretin. To identify residues involved in gating the pIV secretin of filamentous bacteriophage f1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 71 publications
2
59
0
Order By: Relevance
“…This model is supported by the observation that the total amount of PilQ is decreased in the frameshift mutants, meaning that fewer pores that can allow the antibiotics to permeate the outer membrane exist. However, the SDS-resistant oligomer was the form of PilQ least affected by the frameshift mutations, and recent evidence suggests that similar secretins have mechanisms that allow them to close in vivo (28,40,41). In addition, deletion of pilW, the protein required for production of the stable SDS-resistant PilQ multimer (37,39), did not increase penicillin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This model is supported by the observation that the total amount of PilQ is decreased in the frameshift mutants, meaning that fewer pores that can allow the antibiotics to permeate the outer membrane exist. However, the SDS-resistant oligomer was the form of PilQ least affected by the frameshift mutations, and recent evidence suggests that similar secretins have mechanisms that allow them to close in vivo (28,40,41). In addition, deletion of pilW, the protein required for production of the stable SDS-resistant PilQ multimer (37,39), did not increase penicillin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Single-residue substitutions in gates 1 and 2 of the C domain of pIV were reported to change the permeability properties of this secretin in the E. coli OM (21). The PulD peptides whose sequences correspond to gates 1 and 2 in pIV (Fig.…”
Section: Secretins Other Than Puld Form Solute-permeable Pores In Lipmentioning
confidence: 99%
“…Electrophysiology studies also suggested that the pIV secretin channel is tightly closed in vitro, although it allows an Escherichia coli strain lacking maltoporin (LamB) to grow on small maltodextrins (20). The permeability of the pIV channel was increased by changes in the pIV sequence that allowed a LamB-deficient strain to regain its ability to import maltopentose (21). These sequence changes clustered mainly in two regions that were named gates 1 and 2 because of their proposed role in channel gating (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 It is highly conserved and predicted to contain several -strands 36 embedded in the outer membrane to form the actual pore through which transport occurs. 21 The N-terminal periplasmic region displays conservation only in secretins from related secretion pathways 29 and may be involved in substrate recognition, 28,37 gating of the proposed channel 35,38 and DNA binding 39 as well as contributing to subunit oligomerization. 35,40 The atomic structures of periplasmic fragments from two secretins, EscC from enteropathogenic E. coli and GspD from enterotoxigenic E. coli, have previously been determined.…”
Section: (31)mentioning
confidence: 99%